Mechanism of Ru(III) Catalysis in Chloramine-T Oxidation of Some Unsaturated Acids - Saxena, Rashmi (Asian Journal of Chemistry, 2010)
Kinetics of ruthenium (III) catalysed oxidation of maleic and acrylic acids by chloramine-T in presence of alkali have been studied. The results showed first order dependence of rate with respect to oxidant and the catalyst. The effect of [substrate] on the rate was positive only at low substrate concentrations. The variation of [OH–] resulted in a negligible effect on the rate. Sodium perchlorate has a negative effect on the reaction rate. A suitable mechanism in conformity with the kinetic data has been proposed.